Basic Movement Training and Agility in Youth Badminton Athletes - Irgan Agus Kurniawan (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aimed to determine the effect of basic movement training on the agility of badminton athletes under 12 years old. The research focused on evaluating whether a structured basic movement training program could significantly improve agility performance among young badminton athletes. Methodology: This study employed a quantitative experimental approach using a One-Group Pretest–Posttest Design. The sample consisted of 27 male badminton athletes under 12 years old from PB. Bantul Badminton Club selected through purposive sampling. The intervention involved 16 sessions of basic movement training. Main Findings: The results demonstrated a significant effect of basic movement training on agility improvement among badminton athletes under 12 years old. The paired-sample t-test revealed a significance value of 0.000 (< 0.05), indicating a statistically significant difference between pretest and posttest scores. The mean agility score improved from 9.1437 seconds during the pretest to 8.6804 seconds during the posttest. Furthermore, the calculated t-value (6.251) exceeded the critical t-value (2.056), confirming the effectiveness of the training intervention in enhancing agility performance. Novelty/Originality of this study: The novelty of this study lies in the application of a structured basic movement training program consisting of twelve integrated locomotor and non-locomotor movement patterns specifically designed for badminton athletes under 12 years old. Unlike conventional badminton training that primarily emphasizes technical skills, this study highlights the importance of fundamental movement development as a foundation for agility enhancement, providing an innovative and age-appropriate training approach for long-term athlete development.